2006
DOI: 10.1159/000091517
|View full text |Cite
|
Sign up to set email alerts
|

Small for Gestational Age and the Metabolic Syndrome: Which Mechanism Is Suggested by Epidemiological and Clinical Studies?

Abstract: The metabolic and cardiovascular complications associated with in-utero undernutrition have been identified during the past 10 years. Reduced fetal growth is independently associated with an increased risk of development of cardiovascular diseases, the insulin-resistance syndrome or one of its components (i.e., hypertension, dyslipidaemia, impaired glucose tolerance and type 2 diabetes). Insulin resistance appears to be a key component underlying these metabolic complications. Although the mechanism remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 48 publications
8
71
0
4
Order By: Relevance
“…This has been observed in rat and mouse models with bilateral uterine artery ligation or isocalorie low protein nutrition during pregnancy (Simmons et al 2001, Song et al 2008, Cripps et al 2009, Hermann et al 2009). In addition, these data are also supported by human observations (Baker et al 1989, Levy-Marchal & Czernichow 2006. In our mouse model, we cannot fully rule out the impact of the low birth weight of the MIFK/K mice in their observed phenotype.…”
Section: Discussionsupporting
confidence: 80%
“…This has been observed in rat and mouse models with bilateral uterine artery ligation or isocalorie low protein nutrition during pregnancy (Simmons et al 2001, Song et al 2008, Cripps et al 2009, Hermann et al 2009). In addition, these data are also supported by human observations (Baker et al 1989, Levy-Marchal & Czernichow 2006. In our mouse model, we cannot fully rule out the impact of the low birth weight of the MIFK/K mice in their observed phenotype.…”
Section: Discussionsupporting
confidence: 80%
“…Nonetheless, MartinezCordero et al found lower cord blood leptin levels in SGA than adequate for gestational age (AGA) infants [49]. Furthermore, in the Haguenau study, leptin levels were found to be decreased in young adults born SGA, even after correction for gender, BMI and hyperinsulinemia [31]. This could be due to a greater adiposity in adults born SGA.…”
Section: Leptinmentioning
confidence: 93%
“…The thrifty phenotype hypothesis [38] suggests that the fetus adapts to an adverse intrauterine environment by diverting limited nutrients to favor the survival and development of vital organs, such as the brain, at the expense of growth. Important metabolic pathways would be permanently programmed during fetal life, leading to metabolic disturbances in adulthood [31,39]. There is evidence suggesting that the degree of weight gain Finally, elevated plasma FFAs inhibit the insulin signal transduction system [24,113,114].…”
Section: Adipocytokines In Children Born Small For Gestational Agementioning
confidence: 99%
See 1 more Smart Citation
“…13 O fato de crianças nascidas a termo pequenas para a idade gestacional, apresentarem aceleração compensatória no ganho ponderal pós-natal e as grandes para a idade gestacional demonstrarem menor ritmo de crescimento, 13 corrobora com o pressuposto de que o risco para um ganho excessivo de gordura corporal pode derivar da interação entre as consequências da restrição do crescimento intraútero e os fatores genéticos e ambientais pós-natais. 19 A seguir, são apresentados alguns mecanismos envolvidos no favorecimento do aumento de peso e no acúmulo de tecido adiposo após o nascimento, decorrentes ou não da evidente restrição do crescimento fetal. ao aumento dos níveis circulantes de glicose após as refeições, 20 sendo um dos principais fatores de crescimento tanto intra quanto extraútero.…”
Section: Aceleração Do Ganho De Pesounclassified